An Overview of Fly-ash Geopolymer Composites in Sustainable Advance Construction Materials - Bakar M.S.A.; Manar G.; Syamsir A.; Rahman M.R.A.; Saad M.R.; Najeeb M.I.; Alhayek A.; Asyraf M.R.M. (Universiti Putra Malaysia Press, 2025)
Fly-ash geopolymer composites are an exciting advancement in eco-friendly construction materials. Fly-ash has become a sustainable alternative to regular cement because the approach addresses critical concerns in construction, such as high energy use, excessive carbon emissions and the challenge of managing industrial waste. In this review, a brief discussion on how fly-ash geopolymer composites could transform construction practices and reduce their impact on the environment. The construction industry is a major contributor to climate change, whereas industrial byproducts like fly-ash can also be an environmental challenge. Thus, the fly-ash geopolymer composites offer an innovative solution by reusing this waste to create environmentally friendly binding materials. Fly-ash can effectively replace traditional cement in construction, improving the durability and sustainability of buildings. By reducing our reliance on regular cement, these composites could revolutionise construction practices across various industries. Developing and widely adopting fly-ash geopolymer composites could bring substantial benefits. It could significantly reduce the construction industry's carbon footprint and contribute to global efforts to combat climate change. Additionally, ongoing research aims to enhance these composites' strength, heat resistance, and chemical durability, further promoting sustainable construction and supporting a circular economy by turning industrial waste into valuable construction materials. ? Universiti Putra Malaysia Press.